2020
DOI: 10.7759/cureus.7320
|View full text |Cite
|
Sign up to set email alerts
|

Role of 24-hour Helpline Service in the Management of Diabetes During the Holy Month of Ramadan

Abstract: To assess the role of the 24-hour helpline service in the management of diabetes during the holy month of Ramadan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Optimal care of selective patients with T1D with low complication rates may allow RF with improvement in glycemic control and without an increase in hypoglycemia, biometric or metabolic parameters Elamari et al [37] n=34 Morocco Impact of RF on the glycemic control of patients with diabetes prepared for fasting according to the ADA 2010 guidelines Good evaluation of diabetic risk level, focused education, glycemia monitoring, and treatment adjustment by implementing international guidelines enable fasting with a low risk of complications Catic and Jusufovic [38] n=27 Bosnia and Herzegovina Knowledge, practice, and attitudes of physicians treating diabetes regarding the management of diabetes in fasting patients during Ramadan There remains an opportunity for the additional introduction of specialized education and measures into the current practices to improve treatment outcomes and standards of care Ulhaque et al [39] n=102 Pakistan Role of a 24-h helpline service in diabetes management during RF The intervention minimizes diabetic complications, facilitates timely treatment adjustments, and reduces hospital visits and admissions ADA: American Diabetes Association, RF: Ramadan fasting, T1D: Type 1 diabetes…”
Section: Authors Study Size and Site Intervention Evaluated Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal care of selective patients with T1D with low complication rates may allow RF with improvement in glycemic control and without an increase in hypoglycemia, biometric or metabolic parameters Elamari et al [37] n=34 Morocco Impact of RF on the glycemic control of patients with diabetes prepared for fasting according to the ADA 2010 guidelines Good evaluation of diabetic risk level, focused education, glycemia monitoring, and treatment adjustment by implementing international guidelines enable fasting with a low risk of complications Catic and Jusufovic [38] n=27 Bosnia and Herzegovina Knowledge, practice, and attitudes of physicians treating diabetes regarding the management of diabetes in fasting patients during Ramadan There remains an opportunity for the additional introduction of specialized education and measures into the current practices to improve treatment outcomes and standards of care Ulhaque et al [39] n=102 Pakistan Role of a 24-h helpline service in diabetes management during RF The intervention minimizes diabetic complications, facilitates timely treatment adjustments, and reduces hospital visits and admissions ADA: American Diabetes Association, RF: Ramadan fasting, T1D: Type 1 diabetes…”
Section: Authors Study Size and Site Intervention Evaluated Conclusionmentioning
confidence: 99%
“…The role of a 24-h helpline service in the management of diabetes was assessed during the month of Ramadan. [39] A prospective study was conducted in Pakistan (2017-2018). Patients with T1D and T2D who were planning to fast in Ramadan 2018 were included.…”
Section: Authors Study Size and Site Intervention Evaluated Conclusionmentioning
confidence: 99%
“…12 In another meta-analysis of 42 randomized controlled trials, the mean reduction in HbA1c was significantly higher in the telemedicine groups compared with usual care in managing diabetes, especially type 2 diabetes. 13 Furthermore, some authors have been interested in telemedicine applied to the follow-up of diabetics during the 14 Our study showed that telemedicine follow-up of diabetic patients during Ramadan did not achieve better glycemic control than conventional follow-up (variations of glycated hemoglobin in 2019 were -0.61% versus −0.36% in 2020). This could be explained by the COVID context of our study.…”
Section: Discussionmentioning
confidence: 71%
“…This study showed a significant decrease of glycated hemoglobin after Ramadan in type 2 patients with diabetes. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Participants viewed telemedicine as a more convenient alternative, although technological barriers remain a concern. A prospective study assessed the role of a 24‐h Helpline Service for people with diabetes during Ramadan and supported its key role in promoting safe fasting and reducing unnecessary hospital visits and admissions 49 . More than half of the 927 calls were queries related to glucose monitoring data and insulin dose adjustment in T1D.…”
Section: Telemedicinementioning
confidence: 99%